Studi pengembangan unit perbenihan ikan laut di Pulau Gumilamo Kabupaten Halmahera Utara - Koloba, Yitzhak; Sinjal, Hengky J; Kalesaran, Ockstan (Universitas Sam Ratulangi, 2015)
This research intended to evaluate the development strategy of Marine Fish Hatchery Unit at Gumilamo Island, North Halmahera. Analysis SWOT was used to determine the development strategy. Data were collected by questionnaire, interview and literature relevant to the research. SWOT analysis showed the internal and external factors that affected the development of Marine Fish Hatchery at Gumilamo island. The strenght were location, water quality , local government support, and availability of seeds and feed. Weakness were lack of public interest, lack of extension and human resources. Opportunity were the high value of the sale, business opportunities and local government regulation. Treat were dependence on fishing effort and safety. Keywords : hatchery, gumilamo, north halmahera, SWOT analysis